2015
DOI: 10.1038/srep07865
|View full text |Cite|
|
Sign up to set email alerts
|

Electrical Detection of Dengue Biomarker Using Egg Yolk Immunoglobulin as the Biological Recognition Element

Abstract: Nonstructural protein 1 (NS1) is secreted by dengue virus in the first days of infection and acts as an excellent dengue biomarker. Here, the direct electrical detection of NS1 from dengue type 2 virus has been achieved by the measurement of variations in open circuit potential (OCP) between a reference electrode and a disposable Au electrode containing immobilized anti-NS1 antibodies acting as immunosensor. Egg yolk immunoglobulin (IgY) was utilized for the first time as the biological recognition element alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 21 publications
(30 reference statements)
1
34
0
3
Order By: Relevance
“…The lower limit of detection of our ELFI is lower than that of others; 90 ng/mL (Figueiredo et al 2015), 35 ng/mL (Silva et al 2015), 30 ng/mL (Om Parkash 2014).…”
Section: Ns1 Protein Detection Dengue Virus (Denv) Includes a Non-stmentioning
confidence: 60%
“…The lower limit of detection of our ELFI is lower than that of others; 90 ng/mL (Figueiredo et al 2015), 35 ng/mL (Silva et al 2015), 30 ng/mL (Om Parkash 2014).…”
Section: Ns1 Protein Detection Dengue Virus (Denv) Includes a Non-stmentioning
confidence: 60%
“…Figueiredo et al produced IgY against the non-structural protein 1 (NS1) of dengue virus 2 (DENV2). These antibodies were used to compose an immunosensor that was effective in electrically detecting the NS1 protein of DENV2 in standard samples and could be used for dengue 2 diagnosis in biological samples [108].…”
Section: Viral Infections Diagnosismentioning
confidence: 99%
“…NS1 exists in multiple oligomeric forms with molecular weight ranging from 46 to 55 kDa, depending on its glycosylation patterns, that are dependent on the infecting Flavivirus and on the host cells they infect and their different cellular locations (Muller and Young, 2013). Indeed, NS1 detection has gained considerable attention for early diagnostic tests of dengue infection, as it is found in abundance in the serum of patients through early stages of the disease (Parkash and Hanim Shueb, 2015) and consequently many works have been proposed to evaluate the levels of NS1 antigen in buffer and in serum samples (Cavalcanti et al, 2012;Dias et al, 2013;Figueiredo et al, 2015;Silva et al, 2014;Su et al, 2003). Although some authors have reported higher levels of NS1 in secondary infections due to increased viremia (Dussart et al, 2006), others describe the detection of this protein due to low pre-existing virus-IgG immune complexes (Peeling et al, 2010).…”
Section: Introductionmentioning
confidence: 99%